Rota virus genotypes and the clinical severity of Diarrhoea among children under 5 years of age - Ezeonwu Bertilla Uzoma; Chinedu Chukwubuikem; Efe Omoyibo; Oguonu Tagbo (Nigerian Postgraduate Medical Journal, 2016)
Background: Diarrhoeal disease still remains one of the common causes of morbidity and mortality in children under 5 years of age. It is caused notably by the different serotypes of rotavirus. Objectives: To ascertain the prevalence and risk factors for rotavirus diarrhoea in children under 5 years of age seen at Federal Medical Centre, Asaba, and to determine the different serotypes and their relationship with diarrhoea severity. Subjects and Methods: A hospital-based cross-sectional study in which all children under 5 years of age, with diarrhoea had their stool samples tested for rotavirus antigen with enzyme immunoassay. Significant values of variables were determined using t-tests and Chi-square tests as appropriate. Results: One hundred and thirty-two children were studied: 52.3% were males and 46.7% were females. Children 1-11 months of age constitute 49.2%, whereas those 12-59 months were 50.8%. Only 49 (37.1%) children were ELISA positive for rotavirus and of this number, 31 (63.3%) were within 1-11 months of age, P = 0.013. The three most common rotavirus genotypes were G3P[6] in 24.5%, G1P[6] in 12.2% and G12P[8] in 10.2% of the samples, respectively. Duration of vomiting was more prolonged with G3P[6] infection, P = 0.029, whereas dehydration and the overall severity of the diarrhoea were more with G12P[8] infection, P = 0.026 and 0.010, respectively. Conclusion: The emerging G12 rotavirus genotype was isolated in Asaba.